Depression‐like behaviour in mice is associated with disrupted circadian rhythms in nucleus accumbens and periaqueductal grey. (6th November 2015) - Landgraf, Dominic; Long, Jaimie E.; Welsh, David K.
Abstract: An association between circadian rhythms and mood regulation is well established, and disturbed circadian clocks are believed to contribute to the development of mood disorders, including major depressive disorder. The circadian system is coordinated by the suprachiasmatic nucleus (SCN), the master pacemaker in the hypothalamus that receives light input from the retina and synchronizes circadian oscillators in other brain regions and peripheral tissues. Lacking the tight neuronal network that couples single‐cell oscillators in the SCN, circadian clocks outside the SCN may be less stable and more susceptible to disturbances, for example by clock gene mutations or uncontrollable stress. However, non‐SCN circadian clocks have not been studied extensively in rodent models of mood disorders. In the present study, it was hypothesized that disturbances of local circadian clocks in mood‐regulating brain areas are associated with depression‐like behaviour in mice. Using the learned helplessness procedure, depression‐like behaviour was evoked in mice bearing the PER2::LUC circadian reporter, and then circadian rhythms of PER2 expression were examined in brain slices from these mice using luminometry and bioluminescence imaging. It was found that helplessness is associated with absence of circadian rhythms in the nucleus accumbens and the periaqueductal grey, two of the most critical brain regions within the reward circuit. The current study provides evidence that susceptibility of mice to depression‐like behaviour is associated with disturbed local circadian clocks in a subset of mood‐regulating brain areas, but the direction of causality remains to be determined. Abstract : An association between circadian rhythms and mood regulation is well established, and disturbed circadian clocks are believed to contribute to the development of mood disorders, including major depressive disorder (MDD). Lacking the tight neuronal network that couples single‐cell oscillators in the SCN, circadian clocks outside the SCN may be less stable and more susceptible to disturbances, for example by clock gene mutations or uncontrollable stress. We found that helplessness in mice is associated with absence of circadian rhythms in the nucleus accumbens and the periaqueductal gray, two of the most critical brain regions within the reward circuit. Our study provides evidence that susceptibility of mice to depression‐like behavior is associated with disturbed local circadian clocks in a subset of mood‐regulating brain areas, but the direction of causality remains to be determined.